2016
DOI: 10.1016/j.jrp.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Personality development in old age relates to physical health and cognitive performance: Evidence from the Berlin Aging Study II

Abstract: We examine how late-life personality development relates to overall morbidity as well as specific performance-based indicators of physical and cognitive functioning in 1,232 older adults in the Berlin Aging Study II (aged 65-88 years). Latent growth models indicated that, on average, neuroticism and conscientiousness decline over time, whereas extraversion and openness increase and agreeableness remains stable. Higher morbidity and worse grip strength were associated with higher neuroticism. Lower grip strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 84 publications
(135 reference statements)
3
71
1
Order By: Relevance
“…Mueller et al, 2016Mueller et al, , 2017Stephan et al, 2014;Sutin, Zonderman, Ferrucci, & Terracciano, 2013), but the interplay between health and personality development has yet to be studied in the context of retirement. Because retirement itself may help preserve or even improve a person's subjective health (Coe & Zamarro, 2011), associations between health change, retirement, and personality development may be complex.…”
Section: Subjective Healthmentioning
confidence: 99%
“…Mueller et al, 2016Mueller et al, , 2017Stephan et al, 2014;Sutin, Zonderman, Ferrucci, & Terracciano, 2013), but the interplay between health and personality development has yet to be studied in the context of retirement. Because retirement itself may help preserve or even improve a person's subjective health (Coe & Zamarro, 2011), associations between health change, retirement, and personality development may be complex.…”
Section: Subjective Healthmentioning
confidence: 99%
“…This finding adds to existing studies conducted over four to 10 years (Allen et al, 2015; Stephan et al, 2014). It is possible that the long-term functional limitations and depressive symptoms that result from a physically inactive lifestyle (Chang et al, 2016 ; Salvela et al, 2010, 2013) may be reflected in a lower tendency to experience positive emotions, be enthusiastic, and be agreeable (Hakulinen et al, 2015 ; Mueller et al, 2016). Furthermore, less physical activity may restrict social interactions, leading to lower propensity to be sociable and prosocially oriented.…”
Section: Discussionmentioning
confidence: 99%
“…Gerontological studies on aging have found that individuals differ substantially with respect to physical and cognitive declines. While the general trend is towards decreases in strength and perceptual speed (Mueller et al, 2016;Penninx, Deeg, van Eijk, Beekman, & Guralnik, 2001), gradually accumulating chronic disease (Sutin, Zonderman, Ferruci, & Terracciano, 2013), and cognitive decline (Salthouse, 2012), there is substantial variability in these aging processes. Individuals also differ in social changes that come with age.…”
Section: Lifespan Trends In Individual Differences In Personality Changementioning
confidence: 99%
“…retirement homes, independent living, living with family). If these physical, cognitive, and social changes impact personality trait change in old age (Mueller et al, 2016;Sutin et al, 2013;Löckenhoff et al, 2009;Specht et al, 2011), individual differences in physical, cognitive, and social development may spur individual differences in personality development during this life stage. Consistent with this notion, past research has found that the rank-order stability of personality decreases in old age (Briley & Tucker-Drob, 2014;Specht et al, 2011;Wortman et al, 2012).…”
Section: Individual Differences In Change 11mentioning
confidence: 99%
See 1 more Smart Citation